Adsorben Magnetit Terlapis Dimerkaptosilika untuk Adsorpsi Anion Logam [AuCl4]- dan [Cr2O7]- - Ngatijo Ngatijo; Diah Riski Gusti; Abdurrazaq Habib Fadhilah; Resilta Khairunnisah (Jurnal Riset Kimia, 2020)
Adsorbent magnetite-dimercapto-silica (Fe3O4 - DMS) is a synthesis of magnetite with 2,3-dimercapto-1-propanol which has been applied to adsorb anions [AuCl4] - and [Cr2O7]-2. The adsorption process of metal anion [AuCl4]- at pH 5 with a contact time of 100 minutes was found optimum results at an adsorption capacity of 77.58 mg/g and an adsorption efficiency value of 96.975%. While the optimum conditions of metal anion [Cr2O7]-2 after the adsorption process at pH 4 with a contact time of 90 minutes was found an adsorption capacity of 85.0426 mg/g and an adsorption efficiency value of 85.0426%. The adsorption efficiency of metal anions [AuCl4]- is higher than the adsorption efficiency of metal anions [Cr2O7] -2Â